Pendekatan deteksi dini non invasif karsinoma nasofaring - Januarti, Ria Wahyu (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Nasopharyngeal carcinoma is a type of cancer that has a considerable prevalence in Indonesia. Nasopharyngeal cancer is associated with Epstein-Barr virus infection, which also correlates with other factors. These factors are age, genetic, environmental and oral hygiene. Usually, nasopharyngeal cancer is late for diagnosis, so it is always found at an advanced stage. In individuals in risky communities, early detection of nasopharyngeal cancer can be done, without being invasive. The examination that can be done is EBV virus serology analysis and EBV DNA examination. The examination can use simple samples such as nasopharyngeal smear and saliva. This convenience allows early detection of nasopharyngeal cancer so that it can reduce morbidity and mortality.